KIDNEY DISEASE SYMPTOMS AND TREATMENT OF ULTRA-HEALTH - Rakhmonov Bakhrom Bakhtiyorovich (TADQIQOTLAR.UZ, 2024)
Abstract: Kidney diseases in men and women include various pathologies that prevent the normal functioning of these organs of the urinary system. Each of the kidney diseases has its own characteristics, different clinical manifestations and treatment methods. In fact, many kidney diseases are asymptomatic, that is, they occur without symptoms, and patients are not aware of the existing problems with their health. Therefore, it is important to understand what the main kidney diseases are, know their symptoms and treatment.